Blood Transfusion Practice before and after Implementation of Type and Screen Protocol in Emergency Department of a University Affiliated Hospital in Iran - Mostafa Alavi-Moghaddam; Mahmoud Bardeh; Hossein Alimohammadi; Habib Emami; Seyed-Mostafa Hosseini-Zijoud (Emergency Medicine International)
Background. Blood transfusion is the cornerstone of therapy for many serious and common diseases. This study was performed to assess blood transfusion practice before and after implementation of type and screen protocol in emergency department of a university affiliated hospital in Iran, 2012-2013. Methods. An audit was studied before and after the implementation of type and screen protocol. The number of blood transfusions, time interval between blood order and transfusion, cross-match to transfusion ratio (C/T ratio), and transfusion index (TI) were checked. C/T ratio was used as a measure of the efficiency of blood ordering practice. We compared our results before and after implementation of type and screen protocol. Results. In present study after implementation of type and screen protocol, the time interval between requesting blood transfusion and transfusion of blood has decreased significantly (P<0.001). The number of blood transfusions required by actual patients increased significantly from 1/2 to 2 (P<0.001). The average cross-match to transfusion (C/T) ratio got near 1.13 from 1.41 and TI got near 0.91 from 0.58 (P<0.001). Conclusion. The implementation of T&S protocol has been proven to be safe, efficient, and beneficial to the transfusion practice of our hospital from the current study.